Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/tp.0000000000002113
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Race and Disease Etiology Predict De Novo Malignancy Risk After Liver Transplantation: Insights for Future Individualized Cancer Screening Guidance

Abstract: This large dataset demonstrates the effects of ethnicity/race and etiologies of liver disease, particularly NASH as additional risk factors for cancer after LT. Patients with these high-risk characteristics should be more regularly and diligently screened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 30 publications
1
38
0
2
Order By: Relevance
“…The largest study showed a 1.6-fold excess risk of any cancer, and a similar site-specific cancer risk profile to that observed for all people living with a transplanted liver [14] . Non-population based evidence from South Korean patients transplanted for HCC has also generated a similar cancer profile to that described above, as well as an excess risk of leukemia, myeloma, and thyroid cancer [27] . Interestingly, this study found a substantially higher short-compared to long-term risk of cancer, with most cancers diagnosed within the first 12 months of transplantation.…”
Section: Cancer Riskmentioning
confidence: 66%
“…The largest study showed a 1.6-fold excess risk of any cancer, and a similar site-specific cancer risk profile to that observed for all people living with a transplanted liver [14] . Non-population based evidence from South Korean patients transplanted for HCC has also generated a similar cancer profile to that described above, as well as an excess risk of leukemia, myeloma, and thyroid cancer [27] . Interestingly, this study found a substantially higher short-compared to long-term risk of cancer, with most cancers diagnosed within the first 12 months of transplantation.…”
Section: Cancer Riskmentioning
confidence: 66%
“…The probabilities of de novo malignancies post‐LT were higher than those in the age‐matched general population 27 . The screening of de novo malignancies has been reportedly recommended post‐LT 28 . A previous study also revealed the higher mortality rate of de novo malignancy post‐transplant despite the likelihood of earlier cancer detection with careful monitoring along with post‐transplant follow‐up/surveillance.…”
Section: Discussionmentioning
confidence: 97%
“…In post‐LT patients, increasing age, prior malignancies, and multi‐organ transplant have shown to be associated with increased risk . More specifically, male gender, obesity, and diabetes have been shown to be associated with increased risk of solid organ tumors after liver transplant .…”
Section: Discussionmentioning
confidence: 99%
“…17,44,45 More specifically, male gender, obesity, and diabetes have been shown to be associated with increased risk of solid organ tumors after liver transplant. 17,44,45 Pertinent to this case, though the risk of colorectal carcinoma in patients on prolonged immunosuppression was initially felt to be similar to that of the general population, more recent studies have reported up to a twofold increased risk with significantly worse prognosis and outcomes. 16,44,45 Given Rachel Phelan https://orcid.org/0000-0001-5252-9991…”
Section: Discussionmentioning
confidence: 99%